Regulation of Monocyte Adhesion and Type I Interferon Signaling by CD52 in Patients With Systemic Sclerosis. Issue 9 (31st July 2021) - Rudnik, Michał; Rolski, Filip; Jordan, Suzana; Mertelj, Tonja; Stellato, Mara; Distler, Oliver; Blyszczuk, Przemysław; Kania, Gabriela
Abstract : Objective: Systemic sclerosis (SSc) is characterized by dysregulation of type I interferon (IFN) signaling. CD52 is known for its immunosuppressive functions in T cells. This study was undertaken to investigate the role of CD52 in monocyte adhesion and type I IFN signaling in patients with SSc. Methods: Transcriptome profiles of circulating CD14+ monocytes from patients with limited cutaneous SSc (lcSSc), patients with diffuse cutaneous SSc (dcSSs), and healthy controls were analyzed by RNA sequencing. Levels of CD52, CD11b/integrin αΜ, and CD18/integrin β2 in whole blood were assessed by flow cytometry. CD52 expression was analyzed in relation to disease phenotype (early, lcSSc, dcSSc) and autoantibody profiles. The impact of overexpression, knockdown, and antibody blocking of CD52 was analyzed by gene and protein expression assays and functional assays. Results: Pathway enrichment analysis indicated an increase in adhesion‐ and type I IFN–related genes in monocytes from SSc patients. These cells displayed up‐regulated expression of CD11b/CD18, reduced expression of CD52, and enhanced adhesion to intercellular adhesion molecule 1 and endothelial cells. Changes in CD52 expression were consistent with the SSc subtypes, as well as with immunosuppressive treatments, autoantibody profiles, and monocyte adhesion properties in patients with SSc. Overexpression of CD52 led to decreased levels of CD18 and monocyte adhesion, while knockdown of CD52 increased monocyte adhesion. Experiments with the humanized anti‐CD52 monoclonal antibody alemtuzumab in blood samples from healthy controls increased monocyte adhesion and CD11b/CD18 expression, and enhanced type I IFN responses. Monocytic CD52 expression was up‐regulated by interleukin‐4 (IL‐4)/IL‐13 via the STAT6 pathway, and was down‐regulated by lipopolysaccharide and IFNs α, β, and γ in a JAK1 and histone deacetylase IIa (HDAC IIa)–dependent manner. Conclusion: Down‐regulation of the antiadhesion CD52 antigen in CD14+ monocytes represents a novel mechanism in the pathogenesis of SSc. Targeting of the IFN–HDAC–CD52 axis in monocytes might represent a new therapeutic option for patients with early SSc.